Aves ameaçadas de extinção nas unidades de conservação e o efeito da exposição ao fogo no Cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Wildfires are a major problem worldwide, caused mainly by inadequate fire management for the maintenance and development of anthropic activities. Especially in the Cerrado biome, fire is a maintainer of the savanna characteristics, however due to the alteration of the fire regime, such as increased fire frequency, fires have increasingly caused damage to biodiversity. To answer (1) How is the estimated richness of threatened bird species of the Cerrado currently distributed and how is it protected by the current protected areas network? (2) Which protected areas have been most exposed to fire and which have the greatest conservation value for threatened birds? (3) Which protected areas should receive priority efforts for fire prevention and control, with the goal of reducing the exposure of endangered birds? We compiled data with occurrences of endangered bird species obtained from online databases and used climatic environmental variables to produce the potential distribution of these species. The species distributions were modeled with five methods and to produce the binary distribution maps. Jaccard's method was used to assess the similarity of the observed and simulated models. We compiled data on hotspots obtained from the National Institute for Space Research (INPE) and used geographic data from the Ministry of Environment (MMA). We generated maps of hotspots, predicted distribution of birds and protected areas geographic data, the maps were overlaid and information was extracted to generate average values of PAs size, bird richness, fire occurrence and conservation priority. Predicted threatened species richness is highest in the central and southern regions and lowest in the northern region. The mean values of area size and predicted richness between state and federal conservation units showed significant differences, while fire outbreaks and conservation priority did not differ significantly between state and federal. Seventeen protected areas have the highest conservation priority, mostly in areas under state jurisdiction. Of the priority protected areas for conservation, two federal had higher fire outbreaks and predicted threatened species richness, both located in the Federal District. Protected areas the Cerrado demand more attention from the public authorities to mitigate environmental impacts resulting from threats, such as uncontrolled fires. Although there are many state conservation units, they still represent an important portion of areas that allow the occurrence, and consequently, the conservation of these species. The protected areas that showed low predicted species richness and high exposure to fires may be areas with high environmental degradation, and present this condition due to lack of proper management.
Endangered birds in protected areas and the effect of fire exposure in the Cerrado
Keywords: Biodiversidade; Aves ameaçadas; Distribuição predita; Conservação; Biodiversity; Threatened birds; Predicted distribution; Conservation; Biodiversity conservation; Biodiversidade - Conservação; CIENCIAS BIOLOGICAS; OUTROS